Cold War counter-terrorism: the evolution of international counter-terrorism in the RCMP Security Service, 1972–1984. Issue 1 (2nd January 2018) - Hewitt, Steve
Abstract: This piece provides a detailed case study of the evolution of counter-terrorism within a specific domestic security agency of a liberal-democratic state in the context of the Cold War. It does so by examining the creation of a counter-terrorism unit within Canada's Royal Canadian Mounted Police Security Service and how it responded to international terrorism. This occurred in between major terrorist attacks in Canada in 1970 and 1985 and included a growing focus on counter-terrorism even as counter-subversion remained a top priority within a still dominant Cold War domestic security framework. Ultimately, the article, based on thousands of pages of previously secret documents, argues that the Security Service could conceive of in a broader strategic sense the threat of terrorism but found it more challenging, for a variety of reasons, including the dominance of the Cold War and the difficulties around infiltrating ethnic communities, to collect intelligence.